Distorsi Pembacaan Kaum Perennialis Terhadap Tasawuf Dalam Mempertemukan Diversitas Agama-Agama - Dzufikar Akbar Romadlon (Tasfiyah: Jurnal Pemikiran Islam, 2018)
Perennial philosophy, has developed into a perspective in religious studies, in order to find a point to unite religions, which leads to the belief in religious pluralism. In Islam they took the justification of the Sufis such as Muhyi al-din Ibn 'Arabi, Jalal al-din al-Rumi and' Abd al-Karim al-Jilli. According to them, these figures had talked about the point which could unite the religions. Therefore, this paper will explore the readings made by perennialists to find the point, which will reveal the validity of claims referred to the Sufis. In the end, it was known that many perennialists distorted the reading of Sufism texts so that they became in line with their beliefs. Whereas in reality, the Sufis did not initiate these beliefs at all, they even believed that only the Sharia of Islam was right and there was no way to Allah except through the path carried by the Prophet Muhammad.